IFN-γ and IL-2 Secretion after ESAT-6-CFP-10 (EC-610) Fusion Antigen Stimulation from Patients with Active Lung Tuberculosis and Latent Lung Tuberculosis - Bastian; Nova Kurniati; Kemas Ya’kub Rahadiyanto; M. Irsan Saleh; Zen Hafy; Francisca Srioetami Tanoerahardjo; Jusak Nugraha; Eddy Mart Salim (Biomedical Journal of Indonesia, 2020)
The Secretion of IFN-γ and IL-2 After ESAT-6-CFP-10 Fusion Antigen Stimulation in Activeand Latent TB Patients. This study held to discover how immune responses work and to know thepathogenesis of active TB and latent TB patients. This study used PBMC to stimulate T Cells withESAT-6 and CFP-10 antigen fusion, and measure the level of IFN-γ and IL-2 with ELISA antibodysandwich (U-Cytech). 16 ml of blood were drawn to 5 tubes. ESAT-6 CFP-20 inducted one tube withQuantiFERON for IFN-γ assay. The other four tubes were PBMC isolated using Ficoll-Paque, andpre-incubated with stimulation of ESAT-6 CFP-10 fusion antigen for 24-72 hours at 370 C andmeasured using T-Spot and ELISA reader. We got from this study that there are no significantdifferences in IFN-γ levels for both groups with active TB and latent TB. Measurement of IL-2 levelsshowed significant differences between the two group.